Brazilian maritime GDP, social, economic and environmental motivations for its measurement and monitoring - Israel de Oliveira Andrade; Giovanni Roriz Lyra Hillebrand; Thauan Santos; Tarin Cristino Frota Mont'Alverne; Andrea Bento Carvalho (Institute for Applied Economic Research (ipea), 2022)
The interaction between the sea and the economy gives this environment enormous strategic importance. The forms of economic exploitation are diverse and include sectors such as energy, fishing, tourism, transportation, biotechnology, and shipbuilding. For Brazil, country with an extensive coastline and vast maritime space, its relevance is especially evident. In this scenario, it is fundamental to elaborate public policies aimed at maritime economic activities. For this purpose, a survey of the numbers referring to such activities is essential for a correct understanding of their dimension. Thus, the objective of this text is to point out the importance of measuring in a continuous and systematic way the Brazilian Maritime GDP, through a specific methodology, as well as to identify the main motivation for this initiative. Based on the descriptive inference method and on bibliographic survey, it was possible to verify the need to use updated data to support the formulation of public policies and decision-making on the subject, as well as to broaden the debate within other actors, such as academia, private sector and civil society.
Keywords: H41; O13; O25; Q20; Q55; Q56; 330; blue economy; maritime GDP; Blue Amazon; maritime economy; public policies; Science; Technology and Innovation